A Comparative Study between Single-loop and Dual-loop Tracking Control Schemes for MPPT of Solar Tracking System - Mutlag, Ahmed Hussein; Hasan, Alaq F.; Fadhel Jassim, Marwa; Humaidi, Amjad J. (Engineering, Technology & Applied Science Research, 2025)
Solar energy is one of the principal renewable energy sources for electric power generation. However, maximizing the power extraction from solar Photo-Voltaic (PV) systems remains a challenge due to their inherent low conversion efficiency. To address this issue, a Maximum Power Point Tracking (MPPT) controller is necessary to optimize power extraction in a PV system. This paper aims to conduct a comparative study between two distinct MPPT control schemes. The first is a simple single-loop system employing the Perturb and Observe (P&O) algorithm. The second is an advanced dual-loop system integrating the P&O algorithm with a Proportional-Integral (PI) controller. The comparison evaluates the systems’ performance in terms of steady-state accuracy. For this purpose, a MATLAB/Simulink model of a stand-alone PV panel was developed. The proposed MPPT schemes were then implemented on this PV system under varying environmental conditions to assess their ability to track the MPPT. The simulation results indicate that the dual-loop control scheme outperforms the single-loop scheme in terms of steady-state performance, particularly during abrupt environmental changes.